White and some colored marbles as alternative radiation shielding materials for applications - Buyukyildiz, M.; Kilic, A. D.; Yilmaz, D. (Taylor & Francis Ltd, 2020)
In this paper, the radiation shielding parameters such as linear attenuation coefficients (LAC, mu), mass attenuation coefficients (MAC, mu/rho), effective atomic numbers (Z(eff)), effective electron densities (N-eff), half value of layers (HVL), mean free paths (MFP) and buildup factors (exposure (EBF) and energy absorption (EABF)) were investigated for cream (M1), pink (M2), white (M3), maroon (M4) and green (M5) marbles. Attenuation coefficients were measured in the energy region 31.18-661.66 keV photon energies. The values of Z(eff) and N-eff were then calculated using these coefficients with logarithmic interpolation method, and HVLs and MFPs were calculated using the values of LAC of marble samples at the same photon energies. The experimental results were compared with the theoretical values obtained from WinXCom program, and good agreements were observed between the experimental and theoretical results. HVLs and MFPs of all marble samples were compared with those of some concretes, glasses and commercial radiation shielding glasses (SCHOTT Co.). The studied marbles were better radiation shielding materials than standard shielding concretes due to lower HVL and MFP values lower than the ordinary concrete. Finally, EBFs and EABFs of the marbles were calculated in the energy region 0.015-1 MeV up to penetration depths of 40 mfps by Geometric Progression method (G-P), and the results were discussed in terms of photon energies and chemical compositions of the marbles.
Keywords: Marble; radiation shielding; effective atomic number; attenuation coefficient; mean free path; buildup factor